Assessment of soybean (Glycine max) genotypes for resistance toBemisia tabaci and its implications on yield - HARISH, GIRI NAGA; SINGH, RAVINDER; TAGGAR, GAURAV KUMAR; GILL, B S (The Indian Journal of Agricultural Sciences, 2024)
The whitefly, Bemisia tabaci Gennadius (Hemiptera: Aleyrodidae), is a significant pest affecting pulse crops in north India, particularly soybean [Glycine max (L.) Merr.]. The study was carried out during the rainy (kharif) seasons of 2018 and 2019 at Punjab Agricultural University, Ludhiana, Punjab to investigate whitefly populations across 8 soybean genotypes. The study revealed that genotypes SL 1074 and SL 1028 had the lowest whitefly infestations, while DS 3105 exhibited high susceptibility. Whitefly populations, peaking at different stages, were positively correlated with temperature and relative humidity and negatively with rainfall. Significant variations in whitefly population densities were observed across different genotypes and canopy levels, with higher populations in the upper and middle canopies. The avoidable yield losses were estimated in three cultivars recommended for cultivation by the Punjab Agricultural University, with losses ranging from 18.12–27.28%. The insecticide thiamethoxam was effective initially, but whitefly populations increased three weeks after the spraying. Unprotected plots exhibited higher whitefly populations and greater yield losses. Negative correlations were found between whitefly populations and yield parameters, particularly with 100-seed weight. This study underscores the importance of cultivating resistant soybean varieties like SL 1074 and SL 1028 to manage B. tabaci and minimize yield losses.